Impact of Economic Growth on Human Capital, Work Participation, and Emission Reductions: Case Study in Indonesia - Murniati, Murniati; Sulisnaningrum, Ema; Priyanto, Eddy (Asia Pacific Journal of Management and Education (APJME), 2023)
Investments are influenced by the level of education and work participation in Indonesia; this happens the same with Human Capital. The importance of human capital and investment can have an impact on economic growth and emission reductions. Based on the results of previous studies, the demand for studies on economic growth, human capital, labor participation, and emission reductions is increasing. To determine the causal link between variables, this study used "autoregressive vectors" modeling across 21 years from 2000 to 2020. World Bank’s data with the Kementerian Lingkungan Hidup dan Kehutanan are the foundation of this study (KLHK). We take into account Indonesia's economic development, labor force participation, investment, level of education, and emission reductions. Based on some conclusions from this research, we found that increased economic growth will also result in higher labor participation rates. Still, it will also result in a drop in Indonesia's investment climate, which will raise emissions while simultaneously encouraging higher levels of education. As investment declines, labor participation will rise as well. Future research should attempt to associate total investment with the level of labor participation in Indonesia because this study has a flaw in that it only considers "foreign investment", and not the whole amount of investment.